Impact of household proximity to the cycling network on bicycle ridership: The case of Bogotá. (July 2019) - Rodriguez-Valencia, Alvaro; Rosas-Satizábal, Daniel; Gordo, Daniel; Ochoa, Andrés
Abstract: Since the late 1990s, Bogotá has been implementing measures and policies to promote sustainable transportation. For example, to promote cycling, the city built 232 km of segregated bicycle infrastructure between 1998 and 2000. Modal share for bicycles was around 0.58% before the massive introduction of cycling facilities; ten years later, it had increased to 6%. Does this intervention have a differential effect on bicycle ridership for people who live close to the cycling infrastructure? The objective of this paper is to determine the impact of residence proximity to linear bicycle infrastructure in Bogotá on bicycle ridership. The selected evaluation method is the difference-in-difference technique used for the georeferenced 1995 and 2011 Household Transportation Surveys, and which provides information relating to before and after the implementation of the new infrastructure. The difference in the travel behavior of people closer to the bike infrastructure, compared to the rest of the city, provide evidence of the effectiveness of the policy measure. We found that living close to cycling infrastructure in Bogotá has a positive and marginal but significant impact on the odds of an individual choosing a bicycle as his or her main mode of transportation, controlling for socio-economic and environmental characteristics. Results are discussed in the light of bicycle-related transportation policies and the econometric modeling technique applied. Highlights: Proximity to cycling infrastructure increases marginally the likelihood of using this mode of transportation. Effects of policies such as off-street bike-path construction are more localized depending on the age and gender. Depending on socio-economic and trip characteristics, new cycling infrastructure may encourage new cyclists to show up In a developing country context, middle-income population appeared to be less prone to using the bicycle.